PENGARUH KARAKTERISTIK MEREK, DIFERENSIASI PRODUK, KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK TELEPON SELULER BLACKBERRY - Abdullah Syafi'i; Nawazirul Lubis; Sendhang Nurseto (Universitas Diponegoro, 2014)
Trust in brand became the basis of the creation of the customer's brand loyalty considering problems brand to be one of the issues that should be monitored constantly by each company. Increasingly fierce competition and growing customer expectations Blackberry encourage companies to focus more on efforts to retain existing customers, through increased consumer loyalty to the brand. The increase in consumer brand loyalty is influenced by many factors, including brand characteristics, product differentiation and brand trust. The problem in this study was a decrease in the number of BlackBerry users in 2010 amid rise in the number of users in each year over the last 6 years. This study aims to determine whether there is influence between brand characteristics, product differentiation and brand trust on brand loyalty.This research used explanatory research. From 221 research population taked 69 respondents as sample with Simple Random Sampling method. Collecting data used questionnaire. Analysis data used correlation coefficient, determination coefficient, regression analysis, t test, and F test.The Result this research show that brand characteristic, product differentiation and brand trust have positive influence and significant on brand loyalty (with result as bis as 26,9%, 44,9%, and 33,2% for each variable) as well as in simultaneous as big as 52,1% with product differentiation gave biggest influence.For to the Blackberry should still perform periodic evaluations and improvements that can be better compared with other products, and has its own character, must maintain a viable product differentiation for consumers that is based on the quality and features are given, as well as providing design and warranty in accordance with the product the. For further research needs to be conducted research on factors other than the characteristics of the brand, product differentiation and brand trust on brand loyalty as price, equity, consumer satisfaction.